Amphotericin B mediates killing in Cryptococcus neoformans through the induction of a strong oxidative burst (2011)
ABSTRACT: We studied the effects of Amphotericin B (AmB) on Cryptococcus neoformans using different viability methods (CFUs enumeration, XTT assay and propidium iodide permeability). After 1 h of incubation, there were no viable colonies when the cells were exposed to AmB concentrations 1 mg/L. In the same conditions, the cells did not become permeable to propidium iodide, a phenomenon that was not observed until 3 h of incubation. When viability was measured in parallel using XTT assay, a result consistent with the CFUs was obtained, although we also observed a paradoxical effect in which at high AmB concentrations, a higher XTT reduction was measured than at intermediate AmB concentrations. This paradoxical effect was not observed after 3 h of incubation with AmB, and lack of XTT reduction was observed at AmB concentrations higher than 1 mg/L. When stained with dihydrofluorescein, AmB induced a strong intracellular oxidative burst. Consistent with oxidative damage, AmB induced protein carbonylation. Our results indicate that in C. neoformans, Amphotericin B causes intracellular damage mediated through the production of free radicals before damage on the cell membrane, measured by propidium iodide uptake.